Environmental Strategy and Practice : A Reflection from Business Activities of Selected Firms - Rakhmayeva, Adalyat (2013)
The following study focuses on the area of environmental strategies of businesses. The research thesis presents the analysis of relationship between firms’ practices and strategies related to the environment. Multiple case study approach with thematic analysis of secondary data is conducted during the course of the study. The first part of the analysis provides short information about case studies and their relations to the topic. Second part draws attention to the analysis of strategies and results from the case studies. The analysis revealed that unsuccessful environmental actions are rarely linked to strategy, whereas in the opposite case companies enjoy success and cost savings. The major recommendation drawn from the study is that actions not backed up with long term strategic orientation will not bring fruitful results. Therefore, before implementing moving towards environmental sustainability firms should adopt the following steps: assess resources and capabilities and other internal factors, and key management, consider external factors and customer-supplier relationships, consider all stake holders, select environmental vision and act continuously incorporating all dimensions into decision making.